KARAKTERISTIK PENYIMPANAN LENGAS TANAH OPTIMUM PADA SISTEM JARINGAN IRIGASI TETES PIPA PVC DENGAN EMITTER 4LT/JAM - I DEWA GEDE JAYA NEGARA; ANID SUPRIYADI; DEWANDHA MAS AGASTYA; HERI SULISTIYONO; I WAYAN YASA (GANEC SWARA, 2024)
Soil moisture is the most important part of irrigation activities, because it is the result achieved by providing irrigation on a particular land. Likewise, with the application of drip irrigation, soil moisture is also the purpose of irrigation in the planting medium. In multilevel drip irrigation sistems, the potential for soil moisture produced by the irrigation sistem is very important to pay attention to, because the size of the moisture that can be provided will affect the scheduling of the drip irrigation provided. And therefore the ability of an irrigation sistem to provide optimum soil moisture in a particular medium deserves attention, before the sistem is applied to farming activities. For this reason, this test aims to determine the ability to provide soil moisture in a drip irrigation sistem that uses a 4 liter/hour emitter in a 4-tiered drip irrigation network, a polybag planting medium and an irrigation duration of 5 minutes to 20 minutes. The test data analyzed is irrigation and soil moisture distribution data, then the results of the analysis are presented in tabular form and discussed and conclusions are drawn. The test results show that the distribution of drip irrigation water occurs evenly with the optimal application of 41% moisture, and with the application of additional soil moisture of around 6% -7% for an irrigation duration of 20 minutes. The daily decrease in soil moisture that occurred during the three days of testing was found to be around 2% as a result of evaporation